Cellular Models of Aging and Senescence - Kim, Byunggik; Lee, Dong I.; Basisty, Nathan; Dai, Dao-Fu (Cells (Basel, Switzerland), 2025)
Aging, a state of progressive decline in physiological function, is an important risk factor for chronic diseases, ranging from cancer and musculoskeletal frailty to cardiovascular and neurodegenerative diseases. Understanding its cellular basis is critical for developing interventions to extend human health span. This review highlights the crucial role of in vitro models, discussing foundational discoveries like the Hayflick limit and the senescence-associated secretory phenotype (SASP), the utility of immortalized cell lines, and transformative human induced pluripotent stem cells (iPSCs) for aging and disease modeling and rejuvenation studies. We also examine methods to induce senescence and discuss the distinction between chronological time and biological clock, with examples of applying cells from progeroid syndromes and mitochondrial diseases to recapitulate some signaling mechanisms in aging. Although no in vitro model can perfectly recapitulate organismal aging, well-chosen models are invaluable for addressing specific mechanistic questions. We focus on experimental strategies to manipulate cellular aging: from “steering” cells toward resilience to “reversing” age-related phenotypes via senolytics, partial epigenetic reprogramming, and targeted modulation of proteostasis and mitochondrial health. This review ultimately underscores the value of in vitro systems for discovery and therapeutic testing while acknowledging the challenge of translating insights from cell studies into effective, organism-wide strategies to promote healthy aging.